PENGARUH BOPO, CAR, NIM, FDR, NPF Net, ROA TERHADAP ROE PADA PT BANK RAKYAT INDONESIA SYARIAH TBK. - HUSNI MUBAROK (DIRHAM Jurnal Ekonomi Islam, 2021)
The author summarizes the problem formulation which aims to understand the statistical results of the effect of BOPO, CAR, NIM, FDR Net, NPF, ROA on the Profitability at PT BRI Syariah 2009-2020. This research uses a descriptive style by making quantitative case studies. The partial test results that have been carried out based on the Linear Regression Analyze model of the ROA component of Standardized Coefficients Beta shows the most influential component is 0,809 which is able to explain 80,9% very strong interest rates, TCount 4,693 TTable 2,17881 significance value 0,005 0,050 The hypothesis is accepted that the residuals are normally distributed to Profitability and the simultaneous test results that have been launched based on the Summary of Linear Regression Analysis Model together with the independent variable indicator of 0,996 are able to explain 99,6% of the very strong relationship between the dependent variables, FCount 116,023 FTable 4,95 Significance value 0,000 0,050 The accepted hypothesis is that the residuals are normally distributed to Profitability.